The incidence of candidate binding sites for ?-arrestin in Drosophila neuropeptide GPCRs. - Taghert, P.H. (PLoS ONE, 2022)
To support studies of neuropeptide neuromodulation, I have studied beta-arrestin binding sites (BBS's) by evaluating the incidence of BBS sequences among the C terminal tails (CTs) of each of the 49 Drosophila melanogaster neuropeptide GPCRs. BBS were identified by matches with a prediction derived from structural analysis of rhodopsin:arrestin and vasopressin receptor: arrestin complexes [1]. To increase the rigor of the identification, I determined the conservation of BBS sequences between two long-diverged species D. melanogaster and D. virilis. There is great diversity in the profile of BBS's in this group of GPCRs. I present evidence for conserved BBS's in a majority of the Drosophila neuropeptide GPCRs; notably some have no conserved BBS sequences. In addition, certain GPCRs display numerous conserved compound BBS's, and many GPCRs display BBS-like sequences in their intracellular loop (ICL) domains as well. Finally, 20 of the neuropeptide GPCRs are expressed as protein isoforms that vary in their CT domains. BBS profiles are typically different across related isoforms suggesting a need to diversify and regulate the extent and nature of GPCR:arrestin interactions. This work provides the initial basis to initiate future in vivo, genetic analyses in Drosophila to evaluate the roles of arrestins in neuropeptide GPCR desensitization, trafficking and signaling.